Crop pollination by bees - Delaplane, Keith S., (CABI, 2000)
This book aims to synthesize the latest scientific literature into principles and practices relevant to workers in crop pollination. Particular focus is on bee-pollinated crops of significant or emerging economic importance in the temperate developed world, crops for which there is significant literature on bee pollination, and crops for which pollination is historically a limiting factor. Three main sections address the biology of pollination, methods of culturing and conserving bees for optimum pollination, and the pollination requirements and recommendations for individual crops. This last section is dealt with through 42 short chapters on different crops, detailing flowering, pollination requirements and pollinators. The crops covered include arable, vegetable, berry and fruit crops. Appendices list sources of beekeeping supplies, a sample bee-keeper/grower pollination contract, and a table of pesticide toxicity to bees.